Split-face comparison of long-pulse-duration neodymium-doped yttrium aluminum garnet (Nd:YAG) 1,064-nm laser alone and combination long-pulse and Q-switched Nd:YAG 1,064-nm laser with carbon photoenhancer lotion for the treatment of enlarged pores in asian women - Penpun Wattanakrai (2018)
BACKGROUND: Long-pulse and Q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG) 1,064-nm laser used for facial rejuvenation can improve pore size. Topical carbon has been used to enhance efficacy. OBJECTIVE: To compare the efficacy and safety of a 1,064-nm long-pulse Nd:YAG laser alone with that of a combination Q-switched Nd:YAG laser with topical carbon lotion followed by long-pulse Nd:YAG to improve enlarged pores. METHODS: Twenty Thai women randomly received five treatments with a long-pulse Nd:YAG laser on one facial half (LP side) and long-pulse Nd:YAG after carbon-assisted Q-switched Nd:YAG laser on the contralateral side (carbon QS+LP side) at 2-week intervals. Participants were evaluated using digital photography, complexion analysis, and a chromometer. RESULTS: There was significant decrease in pore counts of 35.5% and 33% from baseline on the carbon QS+LP and LP sides, respectively. Physician-evaluated pore size improvement was 67% on the carbon QS+LP sides and 60% on the LP sides. Chromometer measurement showed an increase in skin lightness index. There was no significant difference between the two treatments, although there were more adverse effects on the carbon QS+LP side. CONCLUSION: Long-pulse Nd:YAG 1,064-nm laser improves the appearance of facial pores and skin color. Adding carbon-assisted Q-switched Nd:YAG did not enhance the results but produced more side effects. Laser Engineer Co. Ltd, Bangkok, Thailand loaned and supplied the laser machine and topical carbon used in this study. © 2010 by the American Society for Dermatologic Surgery, Inc.